IMPLEMENTASI PERATURAN MENTERI PUPR RI NOMOR 28/PRT/M/2015 TENTANG PENETAPAN GARIS SEMPADAN SUNGAI DAN GARIS SEMPADAN DANAU TERHADAP BANGUNAN YANG BERDIRI DI SEMPADAN SUNGAI DAERAH KABUPATEN KAMPAR (Studi Kasus Sungai Kampar Wilayah Kecamatan Bangkinan - Salam, Alfitra; Sutrisno, Hafiz; Prayudi Saputra, Rian (Pahlawan Tuanku Tambusai University, 2025)
Riverbanks that are used as a place to build buildings will have a significant impact on the sustainability of the river and is an action prohibited by law. This research aims to examine the extent and find out what are the factors inhibiting the implementation of the Regulation of the Minister of Public Works and Public Housing Number 28 of 2015 in the Kampar Regency Area. The research method used is empirical legal research. The results of this study indicate that the legal implementation of the legal provisions in this study has not been fully implemented. The inhibiting factors are lack of communication, coordination between parties, budget factors and contingents who master the field have not been formed, and there is no solution that can benefit between parties. Suggestions from the author the government must firmly respond to these regulations, always conduct counseling, and immediately propose to relocate the community in the Kampar river border area. Keywords: Implementation, Riverbanks, Prohibition of Building Contruction